Deep renovation and decarbonisation of school buildings – The CIS Roma Scuole Verdi - Carola Clemente; Francesco Mancini; Anna Mangiatordi; Mariangela Zagaria (Agathón)
The contribution illustrates the experience of CIS Roma Scuole Verdi, where the DiAP Research Group of the ‘Sapienza’ University of Rome supported the CSIMU Department of Roma Capitale in launching a process of energy-environmental upgrading and decarbonisation of 111 school buildings distributed across the 15 Municipalities of the City of Rome. Through a systemic and multi-scalar approach, some Key Performance Indicators (KPIs) were identified and monitored, which were significant for energy class, reduction of climate-altering emissions, reduction of energy needs, and supply from renewable sources. The positive contribution of the implemented technological-plant solutions presents a replicability potential, contributing to the intensification of climate actions, with impacts on urban regeneration and the city’s public budgets.